AGE AND OBESITY INTERFERES IN MUSCLE HYPERTROPHY IN RATS UNDERGOING HIIT TRAINING - Diogo Rodrigues Jimenes; Fernanda Cândido; Nilton Rodrigues Teixeira Júnior; Wilson Rinaldi; Carmem Patrícia Barbosa (Arquivos do Mudi, 2023)
Sarcopenic obesity is a condition characterized by the simultaneous presence of obesity andsarcopenia, which is the loss of muscle mass and function. Is a growing concern, especiallyamong the elderly population, and it is important to address both obesity and sarcopeniathrough lifestyle modifications, such as exercise and proper nutrition, to improve overallhealth and quality of life. Our study aimed to evaluate the effect of HIIT training on themuscle fiber area of the EDL muscle in obese rats of different ages. For that, Wistar rats, 7and 12 months old, submitted or not to a HFD diet were subjected to HIIT training, 3 times aweek, on alternate days, for 8 consecutive weeks. After the euthanasia EDL muscles wascollected and processed histologically. Our data showed that HIIT training was able topromote muscle hypertrophy even with consumption of this diet, indicating that practicingthis exercise can stimulate protein synthesis even under conditions of obesity.